Four priorities for new links between conservation science and accounting research. Issue 4 (27th November 2018) - Feger, Clément; Mermet, Laurent; Vira, Bhaskar; Addison, Prue F.E.; Barker, Richard; Birkin, Frank; Burns, John; Cooper, Stuart; Couvet, Denis; Cuckston, Thomas; Daily, Gretchen C.; Dey, Colin; et al.
Abstract: Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.